A "Clearer" View of Pancreatic Pathology: A Review of Tissue Clearing and Advanced Microscopy Techniques. (January 2019) - Hong, Seung-Mo; Noë, Michaël; Hruban, Carolyn A.; Thompson, Elizabeth D.; Wood, Laura D.; Hruban, Ralph H.
Abstract : Although pathologic lesions in the pancreas are 3-dimensional (3D) complex structures, we currently use thin 2D hematoxylin and eosin stained slides to study and diagnose pancreatic pathology. Two technologies, tissue clearing and advanced microscopy, have recently converged, and when used together they open the remarkable world of 3D anatomy and pathology to pathologists. Advances in tissue clearing and antibody penetration now make even dense fibrotic tissues amenable to clearing, and light sheet and confocal microscopies allow labeled cells deep within these cleared tissues to be visualized. Clearing techniques can be categorized as solvent-based or aqueous-based techniques, but both clearing methods consist of 4 fundamental steps, including pretreatment of specimens, permeabilization and/or removal of lipid, immunolabeling with antibody penetration, and clearing by refractive index matching. Specialized microscopes, including the light sheet microscope, the 2-photon microscope, and the confocal microscope, can then be used to visualize and evaluate the 3D histology. Both endocrine and exocrine pancreas pathology can then be visualized. The application of labeling and clearing to surgically resected human pancreatic parenchyma can provide detailed visualization of the complexities of normal pancreatic anatomy. It also can be used to characterize the 3D architecture of disease processes ranging from precursor lesions, such as pancreatic intraepithelial neoplasia lesions and intraductal papillary mucinous neoplasms, to infiltrating pancreatic ductal adenocarcinomas. The evaluation of 3D histopathology, including pathology of the pancreatic lesions, will provide new insights into lesions that previously were seen, and thought of, only in 2 dimensions. Abstract : Supplemental Digital Content is available in the text.